Comprehensive Physiology 1996
DOI: 10.1002/cphy.cp040255
|View full text |Cite
|
Sign up to set email alerts
|

Body Fluid and Energy Metabolism at High Altitude

Abstract: Body Fluid Metabolism at High Altitude Acute hypoxia Body fluid volume and sodium and water metabolism Control of body fluid volume and sodium and water Special conditions influencing body fluid homeostasis Body fluid volume and sodium and water metabolism Control of body fluid volume and sodium and water meta bolism

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 103 publications
1
22
0
Order By: Relevance
“…Prolonged hypoxia is associated with a general hypohydration, i.e., decrease in total body water, plasma volume, extracellular and intracellular water, rather than a redistribution of body fluids toward intracellular compartment [10,11,14]. Furthermore, Krzywicki et al [15] reported that intracellular and extracellular water did not significantly change with rehabilitation from high altitude, supporting the idea that redistribution of body fluids would not primarily account for PV recovery upon RSL.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Prolonged hypoxia is associated with a general hypohydration, i.e., decrease in total body water, plasma volume, extracellular and intracellular water, rather than a redistribution of body fluids toward intracellular compartment [10,11,14]. Furthermore, Krzywicki et al [15] reported that intracellular and extracellular water did not significantly change with rehabilitation from high altitude, supporting the idea that redistribution of body fluids would not primarily account for PV recovery upon RSL.…”
Section: Discussionmentioning
confidence: 98%
“…This phenomenon leads to a rapid increase in hemoglobin concentration and arterial oxygen content, before erythropoiesis brings new red cells into the circulation. PV loss at high altitude is generally attributed to spontaneous hypohydration associated with an increase in diuresis during early acclimatization [10]. High altitude diuresis appears to be primarily related to the increase in peripheral chemoreceptor stimulation, and may also involve reflexes initiated by stretch receptors [9,10,27].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…55 These effects can be further augmented if hypoxemia is induced, as with exposure to high altitudes. [56][57][58] Many of the exercise and exercise training hormonal responses are affected tremendously by environmental factors. In particular, catecholamines, growth hormone, aldosterone, antidiuretic hormone (vasopressin), adrenocorticotropic hormone, and cortisol are susceptible to environmental conditions and show exacerbated responses in various conditions.…”
Section: Procedural-analytic Factorsmentioning
confidence: 99%